The Third Global Coral Bleaching Event on the Marginal Coral Reefs of the Southwestern Indian Ocean and Factors That Contribute to Their Resistance and Resilience - Porter, Sean N.; Sink, Kerry J.; Schleyer, Michael H. (Diversity (Basel), 2021)
Coral reefs reach their southernmost limits in the southwestern Indian Ocean in Maputaland, South Africa. Here, we investigate the recent global coral bleaching event of 2016, the thermal dynamics of these marginal high-latitude reefs and the potential environmental factors regulating the responses of coral communities. Pre-, peak- and post-bleaching surveys of over 9850 coral colonies from 29 genera were undertaken over 3 years across 14 sites spanning 120 km of coastline using point-intercept and visual bleaching index survey methodologies. Bleaching data were related to several environmental variables including temperature, degree heating weeks (DHW), depth, latitude, and upwelling intensity. These reefs have experienced a history of relatively low thermal stress based on DHW. Long-term in situ temperature records nevertheless showed no obvious trend of increase. In situ temperatures also displayed poor relationships, with temperatures predicted by the Representative Concentration Pathway models. Mild coral bleaching with no significant mortality was recorded across sites with taxon-specific bleaching responses evident. Latitude and cumulative daily DHW were significantly related to the bleaching index whereas depth and interactions of depth with latitude and DHW were not. While upwelling of cooler water may offer some refuge to coral communities, especially in the Central and Southern Reef Complexes where it is more pronounced, this may only be transient as the upwelled water may also experience some degree of warming in future, thereby limiting such protection from global warming.